2012
DOI: 10.4103/1947-2714.101993
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of Pneumocystis jirovecii in patients with respiratory tract infections

Abstract: Background:Pneumocystis jirovecii, formerly known as P. carinii, is an opportunistic fungus causing Pneumocystis carinii pneumonia especially in immunocompromised patients.Aim:The aim of this study was to detect P. jirovecii in sputum samples from patients suspected of having respiratory tract infections.Materials and Methods:In this study, 230 acid fast bacilli negative sputum samples from 230 patients presenting with respiratory tract infections submitted to three teaching hospitals’ medical microbiology lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
1
2
Order By: Relevance
“…Another study from the same centre on hospitalised HIV-infected patients, demonstrated that cryptococcal meningitis accounted for 8.8% of all OIs with a 12% case-fatality ratio 18 . PJP accounted for 1% of all AIDS-related mycotic infections in the present study, this is lower than 13% reported from a study in Western Nigeria 31 . While diagnosis in the index study was made clinically; in the study cited above, PJP was diagnosed using a PCR assay.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Another study from the same centre on hospitalised HIV-infected patients, demonstrated that cryptococcal meningitis accounted for 8.8% of all OIs with a 12% case-fatality ratio 18 . PJP accounted for 1% of all AIDS-related mycotic infections in the present study, this is lower than 13% reported from a study in Western Nigeria 31 . While diagnosis in the index study was made clinically; in the study cited above, PJP was diagnosed using a PCR assay.…”
Section: Discussioncontrasting
confidence: 82%
“…PJP accounted for 1% of all AIDS-related mycotic infections in the present study, this is lower than 13% reported from a study in Western Nigeria 31 . While diagnosis in the index study was made clinically; in the study cited above, PJP was diagnosed using a PCR assay.…”
Section: Discussioncontrasting
confidence: 82%
“…For instance in a study in hospitals from the south-western region of Nigeria where 230 acid fast bacilli negative sputum samples from 230 patients presenting with respiratory tract infections, cysts of Pneumocystis jirovecii, formerly known as P. carinii were observed in 15 (6.5%) samples and polymerase chain reaction was positive for 29 (12.6%) samples out of 230 samples examined. The author concluded that P. jirovecii should be included in diagnosis of these infections in that part of the world [11]. In The Gambia, a study looking at healthy young individuals concluded that infection with P. carinii was common [12].…”
mentioning
confidence: 99%